Progressive improvements in patient-reported outcomes with the high-concentration capsaicin patch: a retrospective cohort study in patients with painful diabetic peripheral neuropathy (CASPAR study) - Überall, Michael A.; Kender, Zoltán; Quandel, Tamara; Engelen, Sylvia; Guerra, Lucia Garcia; Fajri, Tawfik; Allen, Samuel M.; Freitas, Rita L.; Eerdekens, Mariëlle H. (Journal of diabetes and its complications, 2025)
Objective - To assess long-term outcomes and tolerability associated with repeated topical high-concentration capsaicin patch (HCCP) treatments in painful diabetic peripheral neuropathy (pDPN). - Methods - CASPAR, a retrospective, non-interventional cohort study of HCCP for neuropathic pain, utilizes real-world data from the German Pain e-Registry. This analysis included 826 patients with pDPN of the hands, feet, or legs receiving ≥1 HCCP with ≥12 months of follow-up. - Results - Significant reductions in 24-ho average pain intensity (API) were seen at baseline to Month 3 (mean 57.5 vs 42.4). Successive treatments generated further improvements; these were lost upon HCCP discontinuation. Patients receiving four HCCPs had a mean API decrease from 59.0 (baseline) to 16.0 (Month 12). A ≥30 % API decrease was achieved at Month 12 in 98.9 %, 90.8 %, 67.7 %, and 22.0 % of patients receiving four, three, two, or one HCCP, respectively. Improvements were observed across sleep, QoL, mood, daily activities, and concomitant pain medication use, with the greatest benefits for patients receiving four HCCPs. Results were consistent across treatment locations. Safety and tolerability aligned with the well-established profile for HCCP, consisting of local application-site reactions. - Conclusion - HCCP is a non-systemic treatment for pDPN associated with increasing improvements in neuropathic pain, sleep, mood, and QoL with successive treatments.